PENGHAMBATAN KSANTIN OKSIDASE OLEH KOMBINASI EKSTRAK TEMPUYUNG (Sonchus Arvensis) DAN SALAM (Syzygium Polyanthum) PADA MENCIT HIPERURISEMIA - ., Dr. Muhtadi; Retnani, Idi; Wahyuningtyas, Nurcahyanti (Universitas Muhamadiyah Surakarta, 2012)
Tempuyung (Sonchus arvensis) and salam (Syzygium polyanthum) leaves can lower uric acid levels were studied. The purpose of this research was to determine mechanism of combined o f tempuyung and salam extracts to reduce uric acid levels by inhibiting xanthine oxidase in hyperuricemic mice. This research used completely randomized design using mice. Fifteen mice were made hiperuricemic by 250 mg/kgBW potassium oxonate p.o then the mice were divided into 3 groups. Group I induced 10 mg/kgBW allopurinol p.o as positive control, group II induced tempuyung-salam p.o each 100 mg/kgBW as the treatment group, group th III induced 0.5 mL/20 gBW distilled water p.o as negative control. Liver was taken 4 day after 2 hours induced potassium oxonate. Data inhibition xanthine oxidase activity was tested with Mann-Whitney. The result showed that the combination of tempuyung-salam extract each 100 mg/kgBW could inhibit xanthine oxidase activity of 51,16%±2,76%, while allopurinol 90,20%±0,16% (p = 0.000).Keyword: Hyperuricemia, Xanthine Oxidase, Sonchus arvensis, Syzygium polyanthum